Frequency of Healing of Fistula in Patients Undergoing Video Assisted Anal Fistula Treatment in High Lying Fistula in Ano - Muhammad Afzal, Muhammad Junaid Shah, Mujeeb Alam Khan, Aftab Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Fistula-in-ano is an abnormal tract that usually connects rectal mucosa and perianal skin thus accounting upto 90% cases with an incidence of 5.6/100.000 in women while 12.3/100.000 in men. Aim: To determine the frequency of healing in patients with high lying fistlua in ano undergoing VAAFT. Study design: Cross-sectional study. Methodology: Patients (n=153) were enrolled during study. All enrolled patients had DRE and proctoscopy before start of treatment. Fistuloscope was used to diagnose high lying fistula during examination. Metronidazole antibiotic was given to all patients both pre and post-surgery. SPSS v.26 analyzed the data. Stratification of healing data was done with respect to age and gender. Post stratification Chi-Squire test was applied with P-value ≤0.05 was taken as significant. Results: Almost 77% were males while rest (23%) patients were females. Results showed healing in 70% of patients while 30% patients failed to heal. Practical Implication: This study showed that VAAFT procedure is safe as a treatment modality in comparison to Anal Fistula Plug and conventional Seton placement for complex fistulas or high anal fistulas thus advocated sphincter saving procedure in our setups. Conclusion: It was concluded that this new surgical technique has advantages like sphincter-saving with small surgical wounds. However, fistuloscopy identifies secondary tracts or chronic abscesses. Keywords: Healing, High Lying Fistlua and VAAFT.